2015
DOI: 10.5455/medarh.2015.69.265-268
|View full text |Cite
|
Sign up to set email alerts
|

Encrustation of the Ureteral Double J Stent in Patients with a Solitary Functional Kidney - a Case Report

Abstract: Introduction:The efficacy of ureteric stents in the management of various urological conditions causing the upper urinary tract obstruction has been extensively proven, and their contribution to urology remains enormous. The clinical use of ureteric stents is associated with several complications. “Stent syndrome,” encrustation, migration and urothelial hyperplasia are the most common problems related to long-term ureteral stenting.Case report:This work presents an interesting case from our practice: a complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For the management of mild encrustation, several studies have reported the role of ESWL followed by retrograde extraction of the DJ stent. In patients with moderate-tosevere encrustations and stone presence, modalities such as transurethral Cystolithotomy (CLT), ureteroscopy, and PCNL are used [13,14]. It has been suggested in a number of studies that the distal part of the stent should be removed first, followed by the proximal end [15].…”
Section: Discussionmentioning
confidence: 99%
“…For the management of mild encrustation, several studies have reported the role of ESWL followed by retrograde extraction of the DJ stent. In patients with moderate-tosevere encrustations and stone presence, modalities such as transurethral Cystolithotomy (CLT), ureteroscopy, and PCNL are used [13,14]. It has been suggested in a number of studies that the distal part of the stent should be removed first, followed by the proximal end [15].…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the implantation of a double-J ureteral stent may be needed. There are absolute indications for stent insertion, which include relief of obstructed pyelonephritis, bilateral ureteral obstruction, ureteric injuries, and post-treatment of urolithiasis in patients with a solitary kidney [ 3 , 4 ]. As no ideal stent, many problems of stent migration, occlusion, encrustation, fragmentation, and stone formation were noticed.…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons recommend stenting to prevent urine leakage and to maintain the anastomosis patent, as postoperatively oedema at the anastomotic site may lead to occlusion of the lumen [3]. However, indwelling ureteric stents can cause problems and significant adverse effects, such as discomfort, infection, migration, and encrustation, which can lead to significant morbidity [4]. Additionally, removing them requires an additional procedure and exposure to anaesthesia.…”
Section: Introductionmentioning
confidence: 99%